Obesity and overweight in Bangladeshi children and adolescents: a scoping review - Rahman, Sholeh (BioMed Central, 2014)
BACKGROUND: Obesity and overweight in children and adolescents is an emerging public health concern alongside under-nutrition in low and middle income countries. Our aim was to conduct a scoping review of literature to ascertain what is known about childhood and adolescent overweight and/or obesity in Bangladesh. METHOD: Using the scoping review based on York methodology, a comprehensive search of published academic articles, conference proceedings and grey literature was carried out through PubMed, BanglaJOL, Google and Google scholar limited to English-written papers. We summarized prevalence, risk factors and health outcomes of obesity/overweight in young children and adolescents aged between 0 to 19 years old in Bangladesh and highlighted use of different reference standards to measure childhood obesity. RESULTS: In total 21 studies met the inclusion criteria. Nearly all of the reviewed articles used data from cross sectional studies, while only two used case–control design. Overall thirteen studies (62%) were primary research and eight (38%) included secondary data. Studies indicated an increasing trend in childhood obesity over time. Prevalence ranged from less than 1% to 17.9% based on different reference standards, with higher percentage amongst urban children across different age groups and sexes. CONCLUSION: This review demonstrated paucity of comprehensive literature on childhood obesity in Bangladesh, which might be explored through population-based prospective studies based on strong methodology and uniform reference standards. Sustainable and scalable preventative measures targeting high risk groups are required to avoid further rise.